2015
DOI: 10.1080/20932685.2014.971491
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of fashion visual merchandising and its role as a brand positioning device

Abstract: In today's globally competitive and dynamic fashion environment every clothing and lifestyle brand, from the largest luxury conglomerate to the independent market stall trader, utilises one if not more elements and principles of visual merchandising (VM). This exploratory study aimed to investigate this under-researched marketing tool within the context of a window display's role in communicating the brand's identity and position in the marketplace. Using a qualitative two-phase approach of nonparticipant stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
0
6
0
3
Order By: Relevance
“…For Park, Jeon and Sullivan (2015) in-fashion and attractiveness visual merchandising can influence positively in brand attitude and purchase intention. According to Nobbs, Foong and Baker (2015) the main elements of window display from the point of view of a non-participant observation and the visual merchandisers interviewed are color and lighting. However, the approach is different depending on the position that VM plays in the market place.…”
Section: Resultsmentioning
confidence: 99%
“…For Park, Jeon and Sullivan (2015) in-fashion and attractiveness visual merchandising can influence positively in brand attitude and purchase intention. According to Nobbs, Foong and Baker (2015) the main elements of window display from the point of view of a non-participant observation and the visual merchandisers interviewed are color and lighting. However, the approach is different depending on the position that VM plays in the market place.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the three qualitative studies identified, the methods were Grounded Theory (Law, Wong & Yip, 2012) and case study (Nobbs, Foong & Baker, 2015). The studies used interviews for data collection (Law et al, 2012;Nobbs et al, 2015) and focus group (Yu, Tullio-Pow & Akhtar, 2015). Nobbs et al (2015) adopted the observation collection technique and the interviews above.…”
Section: Analysis Of Methodological Aspectsmentioning
confidence: 99%
“…The studies used interviews for data collection (Law et al, 2012;Nobbs et al, 2015) and focus group (Yu, Tullio-Pow & Akhtar, 2015). Nobbs et al (2015) adopted the observation collection technique and the interviews above. For data analysis, studies adopted different techniques, namely:…”
Section: Analysis Of Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…El expositor del producto y el escaparate son "elementos ubicuos y prominentes de la estrategia del comercio minorista poco estudiados como técnica de comunicación" (Sen et al, 2002, p. 277). Y el escaparate como elemento principal en el entorno competitivo y dinámico de la moda (Nobbs et al, 2015). En la era omnicanal se ha demostrado que elementos de branding como el tour virtual de fotos de la tienda real incrementan la intención de visita a la tienda (Baek et al, 2020).…”
Section: Interacción Del Consumidor Con Los Elementos Visualesunclassified